Distance travelled to purchase alcohol and the mediating effect of price. (March 2017) - Hobday, M.; Lensvelt, E.; Gordon, E.; Liang, W.; Meuleners, L.; Chikritzhs, T.
Abstract: Objectives: Little research has been done into the distance travelled by consumers to purchase alcohol, whether this is influenced by demographic characteristics or drinking levels of consumers, and the effect of price on purchase distance. This study aimed to explore distances drinkers were prepared to travel to purchase alcohol at on- and off-site outlets and how these decisions were affected by price discounting. Study design: Online survey. Methods: The study, including 831 alcohol consumers aged 18 years and older living in Australian capital cities, was undertaken in 2012. The survey was used to gather data on the distances which participants anticipated that they usually travelled to purchase alcohol. The data provided insight into which factors influence where participants would choose to purchase alcohol and the possible effects of price discounts on purchase distance. Results: Most participants would choose to travel less than 10 km to purchase alcohol. Data indicated that price discounting might increase the purchase distance that most participants would be prepared to travel to purchase alcohol; this was more marked regarding off-site outlets and among high-risk drinking groups including young males and participants with risky drinking levels. Conclusions: Price discounting affects hypothetical purchase distance choices, indicating the importance of price when implementing alcohol control policies. Purchase distance might be more affected by price discounting among consumers visiting off-site outlets, but less useful when exploring associations with on-site outlets. Highlights: Most metropolitan Australians would travel less than 10 km to purchase alcohol. Price discounting increases the distance travelled to purchase alcohol. Discounting affects distance travelled to liquor stores more than to pubs. Riskier drinkers appear more influenced by price discounting than other drinkers.